2010
DOI: 10.1051/epjconf/20100622010
|View full text |Cite
|
Sign up to set email alerts
|

Advanced acoustic emission analysis of brittle and porous rock fracturing

Abstract: Abstract. Analysis of Acoustic Emission (AE) induced during brittle and porous rock fracturing at variety of loading conditions has been performed. On the base of advanced analysis of AE parameters, ultrasonic velocities and mechanical data we found that regardless of applied loading conditions the process of rock fracture can be separated into two main stages: (A) accumulation of non-correlated cracks localized almost randomly in the whole volume of uniformly stressed rock. (B) Final stage of sample fracturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Similarly, when σ 3 = 70 MPa, the ratio increased from 1.75 (at σ 2 = σ 3 ) to 2.44 (at σ 2 = σ 1 ). Similar findings have also been reported in other studies . Stanchits et al performed conventional triaxial tests on intact samples of granite and sandstone rocks under different confining pressures of σ 3 = 10 and 60 MPa and employed acoustic emission to study the impact of the confinement on the tensile and shear components of cracking in the rock samples.…”
Section: Simulation Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Similarly, when σ 3 = 70 MPa, the ratio increased from 1.75 (at σ 2 = σ 3 ) to 2.44 (at σ 2 = σ 1 ). Similar findings have also been reported in other studies . Stanchits et al performed conventional triaxial tests on intact samples of granite and sandstone rocks under different confining pressures of σ 3 = 10 and 60 MPa and employed acoustic emission to study the impact of the confinement on the tensile and shear components of cracking in the rock samples.…”
Section: Simulation Resultssupporting
confidence: 75%
“…Similar findings have also been reported in other studies . Stanchits et al performed conventional triaxial tests on intact samples of granite and sandstone rocks under different confining pressures of σ 3 = 10 and 60 MPa and employed acoustic emission to study the impact of the confinement on the tensile and shear components of cracking in the rock samples. They observed a larger contribution of shear cracks relative to tensile cracks with higher confining pressure, along with compaction bands, owing to grain crushing and pore collapse.…”
Section: Simulation Resultsmentioning
confidence: 80%
“…A plethora of laboratory rock deformation experiments, for example, are known to show sequences of much smaller failures preceding a through-going rupture 2 , 3 . These laboratory tests also showed that shortly before failure the spatial correlation of small failures increased significantly 4 . In the past, such small-scale failure processes have not been commonly observed for natural earthquakes along plate boundaries.…”
Section: Introductionmentioning
confidence: 81%
“…A plethora of laboratory rock deformation experiments, for example, are known to show sequences of much smaller failures preceding a through-going rupture 2,3 . These laboratory tests also showed that shortly before failure the spatial correlation of small failures increased significantly 4 . In the past, such small-scale failure processes have not been commonly observed for natural earthquakes along plate boundaries.…”
mentioning
confidence: 81%